2012
DOI: 10.1002/jsfa.5944
|View full text |Cite
|
Sign up to set email alerts
|

Influence of exogenously applied abscisic acid on carotenoid content and water uptake in flowers of the tea plant (Camellia sinensis)

Abstract: In summary, this paper reports, for the first time, the carotenoid profile and content of tea flowers. The study revealed that carotenoids in tea flowers are an interesting target in respect of possible applications of tea flower extracts as well as biological functions of abscisic acid during floral development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
(50 reference statements)
1
5
0
Order By: Relevance
“…However, ABA treatment may have negative effects on carotenoids accumulation. The content of total carotenoids in tea plant (Camellia sinensis) flowers were reduced by ABA treatment [32]. Similar results were found in the callus of Scutellaria baicalensis after ABA treatment [33].…”
Section: Discussionsupporting
confidence: 72%
“…However, ABA treatment may have negative effects on carotenoids accumulation. The content of total carotenoids in tea plant (Camellia sinensis) flowers were reduced by ABA treatment [32]. Similar results were found in the callus of Scutellaria baicalensis after ABA treatment [33].…”
Section: Discussionsupporting
confidence: 72%
“…However, in the present study, PSY transcripts are reduced or unaffected and are probably not predominantly affected by ABA. Exogenous application of ABA shows contrasting effects depending on plant tissue and species ( Baldermann et al., 2013 ; Barickman et al., 2014 ; Liu et al., 2020 ). Overall, no conclusion can be made about ABA being involved in mediating carotenoid accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Barickman et al (2014a) and Li et al (2010) found that exogenous applications of ABA directly to the root tissue in the hydroponic solution increased carotenoid concentrations in the leaf tissue of lettuce (Lactuce sativa) and 'Micro' tomato. On the other hand, Baldermann et al (2013) demonstrated that exogenously applied ABA decreased total carotenoids in tea (Camellia sinensis) plant flowers. These results were similar to the current study.…”
Section: Discussionmentioning
confidence: 99%